The Strong Case Approach in Behavioral Archaeology - Schiffer, Michael B. (Foundations of Archaeological Inquiry Ser, 2017)
Intro -- Contents -- List of Figures -- List of Tables -- Preface -- 1. The Strong Case Approach - Michael Brian Schiffer and J. Jefferson Reid -- 2. Strong Cases, Mortuary Ritual, and Sodalities: Examples from Grasshopper Pueblo, Arizona - Stephanie M. Whittlesey -- 3. Agricultural Commitment in the Grasshopper Region - John R. Welch and Joseph A. Ezzo -- 4. Pots and the Stories They Tell: Whole Vessel Assemblages as Strong Analytic Cases - Scott Van Keuren -- 5. The Ritual Retirement of Chodistaas Pueblo: A Strong Analytic Case - Barbara K. Montgomery -- 6. Snaketown in Culture- Historical Perspective - J. Jefferson Reid -- 7. Hohokam Chronology and the Interpretation of Radiocarbon Dates - Michael Brian Schiffer -- 8. Hearths, "Kivas," and Households at the Pigg Site: An Architectural Strong Analytical Case from Southwest Colorado - Charles R. Riggs -- 9. Inferring Identity and Social Divisions in a Multiethnic Historical Cemetery: The Alameda-Stone Cemetery in Tucson, Arizona - Michael Heilen -- 10. The Strong Case Approach in Ethnoarchaeology - James M. Skibo, Margaret E. Beck, and William A. Longacre -- 11. Perceiving the Protohistoric: When Weak Signatures Represent the Strongest Cases - Deni J. Seymour -- 12. Strong Cases and the Historical Record: The Case of Portable Radios with Subminiature Tubes - Michael Brian Schiffer -- 13. Strong Methods in All Cases - Mark E. Harlan -- List of Contributors -- Index.